Daily field checking list by Walter Rosene, April 9, 1933 - Rosene, Walter M., Sr., 1880-1941et al; Iowa Ornithologists' Unionet al
Bird checklist dated April 9, 1933. This checklist was used by Walter Rosene to record birds sighted with Bob Walker around North Bridge between 8:00 and 11:00, and Little Wall Lake between 2:00 and 6:00. Plustek--flatbed